(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Prediabetes is determined on the bases of glycemic parameters, which are above normal but below diabetic thresholds. Prediabetes is associated with the presence of insulin resistance and ?-cells dysfunction. N-acetyl cysteine (NAC), as a safe and inexpensive medication, is commercially accessible since long-time ago. This drug is not found in natural sources, although cysteine is present in some meals like chicken and turkey meats, garlic, yogurt, and eggs. NAC prevents apoptosis and oxygen related genotoxicity in endothelial cells by increasing intracellular levels of glutathione and decreasing mitochondrial membrane depolarization reaction. Objective: To evaluate the effects of NAC administration on glucose homeostasis parameters in prediabetic patients. Methods: This study included, 25 patients treated with dietary control and life style modifications for 12 weeks, 25 patients treated with NAC (600 mg) oral tablets twice daily plus dietary control and life style modifications for 12 weeks. Other 20 in addition to 50 patients to have an idea about the normal values of study parameters and in order to assess how much the drug used in the study were able to normalize the abnormal parameters. Results: NAC demonstrated a significant decrease in the fasting blood sugar, HbA1c, fasting Insulin and insulin resistance at the end of 12 weeks (P